In vitro simulator with numerical stress analysis for evaluation of stent‐assisted coiling embolization in cerebral aneurysm treatments. Issue 4 (27th December 2013) - Shi, Chaoyang; Kojima, Masahiro; Tercero, Carlos; Najdovski, Zoran; Ikeda, Seiichi; Fukuda, Toshio; Arai, Fumihito; Negoro, Makoto
Abstract Background There are several complications associated with Stent‐assisted Coil Embolization (SACE) in cerebral aneurysm treatments, due to damaging operations by surgeons and undesirable mechanical properties of stents. Therefore, it is necessary to develop an in vitro simulator that provides both training and research for evaluating the mechanical properties of stents. Methods A new in vitro simulator for three‐dimensional digital subtraction angiography was constructed, followed by aneurysm models fabricated with new materials. Next, this platform was used to provide training and to conduct photoelastic stress analysis to evaluate the SACE technique. Results The average interaction stress increasingly varied for the two different stents. Improvements for the Maximum‐Likelihood Expectation‐Maximization method were developed to reconstruct cross‐sections with both thickness and stress information. Conclusions The technique presented can improve a surgeon's skills and quantify the performance of stents to improve mechanical design and classification. This method can contribute to three‐dimensional stress and volume variation evaluation and assess a surgeon's skills. Copyright © 2013 John Wiley & Sons, Ltd.